29 Cotton Gin Trash Processing, Quality and Safety Impacts on Feeding Recommendations for Beef Cattle. (8th March 2022) - Zessin, Peyton; Jacobs, Joshua; Justice, Maggie M; Mullenix, M Kim; Dillard, Leanne L; Rodning, Soren P; Tigue, Alex A
Abstract: Cotton gin trash is a byproduct of the cotton industry that consists of any remaining plant material leftover after the ginning process. The objective of this study was to determine intake, animal performance, and safety of using loose or baled gin trash in beef cattle diets. Sixteen crossbred, non-lactating, gestating cows and 8 crossbred, gestating heifers were randomly assigned to one of two groups consisting of 8 cows and 4 heifers per group for a 60-day intake trial utilizing the Calan Gate ® system. After a training period, each group was assigned to receive one of two dietary treatments: 1) ad libitum baled cotton gin trash or 2) ad libitum loose cotton gin trash, each with 2.2 kg of a 50:50 mixture of corn gluten feed and soyhull pellets per day to meet nutritional requirements for their stage of production. Animal body weight (BW) and body condition scores (BCS) were recorded at days 0, 30, and 60. Jugular blood samples were collected weekly to monitor clinical animal immune responses due to feeding cotton gin trash containing cotton defoliant residue (4.84 ppm and 1.98 ppm tribufos for baled and loose, respectively). Intake was greater (P < 0.0001) for cattle consuming loose than baled gin trash. All cattle maintained or gained BW across treatments during the trial. On average throughout the study cattle consuming baled gin trash had greater BCS (P = 0.0173) than cattle fed loose gin trash, although animals maintained a BCS of 6 or greater during the study. Red blood cell count, hemoglobin, hematocrit, and white blood cell count were within normal ranges for beef cattle during the trial. Cotton gin trash in either loose or baled form can be used to maintain non-lactating, bred cows with little additional energy supplementation, providing an outlet for cotton byproduct usage in beef operations in the Southeast United States.